Intestinal-type adenocarcinoma of the vagina: clinico-pathologic features of a common tumor with a rare localization - BROGGI, G.; PIOMBINO, E.; MAGRO, G.; VECCHIO, G.M. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
Intestinal-type adenocarcinoma is a rare primary vaginal carcinoma and considerably more uncommon than metastatic lesions which represent the most frequent malignancy at this anatomic site. Among all malignant tumors, colorectal, breast and female genital tract carcinomas have the tendency to metastasize to the vagina. As morphologic and immunohistochemical features of intestinaltype adenocarcinoma occurring primarily in the vagina are not specific, clinical and radiologic information is crucial to exclude a metastatic lesion. Herein we present a rare case of intestinal-type adenocarcinoma from a villous adenoma, presenting as a polypoid mass in the posterior wall of vaginal introitus of 51-year-old menopausal woman. To the best of our knowledge, only 19 cases of intestinal-type adenocarcinoma of the vagina have been reported in the English literature so far. Notably the origin from a previous villous adenoma has been well documented only in a few cases.